Biochemical Profile and Assessment of risk factors for Patients Diagnosed with Myocardial Infarction in AlRamadi City, Iraq - Saleh, Marwan Mahmood (Kurdistan Journal of Applied Research, 2017)
Myocardial infarction (MI) continues to be a major cause of mortality and also death at early ages all over the world. This study is undertaken to evaluate the effect of MI on the levels of lipid profile, two enzymatic markers, fasting blood sugar (FBS), urea, creatinine and total serum bilirubin (TSB), rather than to assess the risk factors which lead to MI and its relation to these variables. The sample of the study consisted of (50) patients admitted to the Cardiac Care Unit in Al-Ramadi General hospital. MI patients had significantly (P?0.05) higher levels of triglyceride (TG) (201.4 mg/dl) as compared with the controls (142.8 mg/dl), while high density lipoprotein (HDL) significantly (P?0.05) decreased in patients (42.24 mg/dl) compared with control group (58.7mg/dl). Total cholesterol (TC) (183.6 mg/dl) and low density lipoprotein (LDL) (109.3mg/dl) were not affected significantly (P?0.05) in MI group when compared with control group with the average of (172.2 mg/dl), (116 mg/dl) respectively. Aspartate aminotransferase (AST) increased significantly (P?0.05) in patients (61.38 IU/L) compared to the control group (23.5 IU/L) , while there was no significant (P?0.05) difference in alkaline phosphatase (ALP) between MI and control group. Levels of fasting blood sugar (FBS) in the serum of MI group (206 mg/dl) increased significantly (P?0.05) comparing with the control group (122.1 mg/dl). This study showed increase in urea (55.6 mg/dl) and creatinine (1.26 mg/dl) levels in the MI group contrast with the control group which its mean was (29.8 mg/dl), ( 0.85 mg/dl) respectively. There was no difference in the level of TSB. Findings of this study, stating differences in levels of some biochemical parameters can use as a biomarker of myocardial infarction. There is an increase in the incidence of myocardial infarction and some differences in the level of parameters in the presence of one or more major risk factors.